2022
DOI: 10.5455/ovj.2022.v12.i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Empirical case report of the mechanical properties of three spayed canine lumbar vertebrae

Abstract: Background: Today, animals, like humans, suffer from spinal illnesses, which are aggravated in old age. Much emphasis is placed on diagnosis and treatment, but little focus is given to the spine's mechanical properties. Degenerative spine diseases are a major problem throughout the world. According to the World Health Organization, osteoporosis is a world-class public problem that reduces bone mass, resulting in bone fracturing and increased risk of bone fracturing. Therefore, the mechanical investigation of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…All curve-fitting coefficients C ik and D ik for vertebra loading and unloading in cyclic load experiments and in vertebra load until fracture experiments are collected into the coefficients data file. This file, with 491 rows of coefficient data, can be found in the Supplementary Material [20]. All experimental and fitted stress-stretch curve images (Figures S1-S128) can be downloaded from the same open data cloud server.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All curve-fitting coefficients C ik and D ik for vertebra loading and unloading in cyclic load experiments and in vertebra load until fracture experiments are collected into the coefficients data file. This file, with 491 rows of coefficient data, can be found in the Supplementary Material [20]. All experimental and fitted stress-stretch curve images (Figures S1-S128) can be downloaded from the same open data cloud server.…”
Section: Resultsmentioning
confidence: 99%
“…This has impelled researchers to identify the best-fitting curve for an accurate description of vertebra stress-stretch curves in external load experiments using canine vertebrae. The first such attempt involved the application of seventh-order polynomials for stress-time and second-order polynomials for stretch-time relations in a parametric form of the stress-stretch curve [13]. During the investigation of soft biological tissues, such as a canine aorta, in opposite tension tests, we have found that the stress-stretch relations of the aorta can be approximated by a logistic function [14].…”
Section: Introductionmentioning
confidence: 99%
“…An animal carcass was used following the same principle applied in our previous experiment [16]. A short overview is provided below.…”
Section: Real-time Experimentsmentioning
confidence: 99%
“…Tests of the axial compression, extension, and flexion were conducted, and the resultant hysteresis loops were analyzed [15]. In addition, we have examined the mechanical properties of the three lumbar vertebrae, concentrating specifically on the hysteresis loops discovered in the aforementioned paper [16].…”
Section: Introductionmentioning
confidence: 99%
“…However, larger animals, such as sheep, can also be used ( Turner, 2001 , 2002 ; Zarrinkalam et al ., 2009 ), and it is possible to investigate rabbits, dogs, and other larger animals ( Reinwald and Burr, 2008 ; Kaveh, 2010 ; Reinwald and Burr, 2011 ). The mechanical qualities of the spine have a significant impact on the development of the disease; in our most recent publication, we analyzed the mechanical properties of canine lumbar vertebrae ( Kostenko et al ., 2022a , 2022b ).…”
Section: Introductionmentioning
confidence: 99%